2020
DOI: 10.3390/molecules25040836
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic Acid as a Candidate in a Phenotypic Profiling Cardio-/Cytotoxicity Cell Model Induced by Doxorubicin

Abstract: Advances in cancer treatment have led to significant improvements in long-term survival in many types of cancer, but heart dysfunction and heart failure, associated with cancer treatment, have also increased. Anthracyclines are the main cause of this type of cardiotoxicity. In this study, we describe a combined experimental and cell morphology analysis approach for the high-throughput measurement and analysis of a cardiomyocyte cell profile, using partial least square linear discriminant analysis (PLS-LDA) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…A high-throughput in vitro phenotypic profiling for toxicity prediction (HIPPTox) system predicted pulmonotoxicity more accurately than cell viability assays in human lung cell lines 90 . Image-based profiling identified rosmarinic acid as a candidate with cardioprotective effects against the toxicity of doxorubicin 91 . This approach also revealed the toxic effects of bisphenol A and its analogues on a testicular cell co-culture model by simultaneously measuring multiple adverse end points such as changes to nuclear morphology and cytoskeletal structure 92 .…”
Section: Lead Generationmentioning
confidence: 99%
“…A high-throughput in vitro phenotypic profiling for toxicity prediction (HIPPTox) system predicted pulmonotoxicity more accurately than cell viability assays in human lung cell lines 90 . Image-based profiling identified rosmarinic acid as a candidate with cardioprotective effects against the toxicity of doxorubicin 91 . This approach also revealed the toxic effects of bisphenol A and its analogues on a testicular cell co-culture model by simultaneously measuring multiple adverse end points such as changes to nuclear morphology and cytoskeletal structure 92 .…”
Section: Lead Generationmentioning
confidence: 99%
“…The stimulation of heme oxygenase-1 (HO-1), which reduces the production of reactive oxygen species, promoted the expression of various proteins such as histone deacetylase, GATA binding protein 4, and troponin13. These findings suggested the therapeutic benefit of RA with special reference to the cancer therapy-related cardiac dysfunction [59].…”
Section: Cardiomyocytementioning
confidence: 84%
“…On the contrary, there is evidence that the antioxidant activity of Rosmarinic Acid can limit the toxicity exerted by chemotherapy in human HL-60 promyelocytic leukemia cells [ 103 ]. Additionally, in vivo studies have shown that Rosmarinic Acid decreased the hepatic and renal toxicity induced by methotrexate, as well as the cardiotoxicity of doxorubicin [ 39 , 104 , 105 ]. In a randomized, placebo-controlled trial in BC patients, oral intake of Prunella vulgaris L., rich in Rosmarinic Acid, inhibited chemotherapy (taxanes) side effects, namely neutrophil-reduced fever and anemia [ 106 ].…”
Section: The Role Of Natural Products In Human Healthmentioning
confidence: 99%